2009
DOI: 10.1021/jp9012587
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Spreading Solvent Evaporation Time in Langmuir Monolayers

Abstract: Supporting InformationAll UV measurements were performed on a Hewlett-Packard 8452A diode array spectrophotometer fitted for air-water interface measurements. A detailed description of the experimental setup was published elsewhere 1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…For adsorption experiments to different lipid monolayers, the lipids were spread at the airwater interface to reach the desired final surface pressure. Thirty minutes were required for solvent evaporation and film stabilization [17]. Then bacillomycin D was injected at different concentrations into the subphase.…”
Section: Adsorption Experiments At Constant Surface Areamentioning
confidence: 99%
“…For adsorption experiments to different lipid monolayers, the lipids were spread at the airwater interface to reach the desired final surface pressure. Thirty minutes were required for solvent evaporation and film stabilization [17]. Then bacillomycin D was injected at different concentrations into the subphase.…”
Section: Adsorption Experiments At Constant Surface Areamentioning
confidence: 99%
“…Thirty minutes was required for solvent evaporation and film stabilization. 15 Mycosubtilin was then injected at a final concentration of 0.545 μM into the subphase. The lipopeptide adsorption at the airÀwater interface, measured by tensiometry, was followed as an increase in surface pressure.…”
Section: ' Materials and Methodsmentioning
confidence: 99%
“…Lipids (in hexane–ethanol at 0.545 mM) were spread at the air–water interface to reach the desired final surface pressure. Thirty minutes was required for solvent evaporation and film stabilization . Mycosubtilin was then injected at a final concentration of 0.545 μM into the subphase.…”
Section: Methodsmentioning
confidence: 99%
“…Maximum surface pressure did not exceed 0.2 mN/m upon compression during the three cycles, indicating that the spreading solvent is not surface active. As mentioned in section 2.3.9.1 in Chapter 2, spreading solvents such as chloroform, toluene, and benzene have been previously shown to not significantly surface active when the maximum changes in surface pressure upon the compression 105. 4.3.2.…”
mentioning
confidence: 97%
“…-9. Maximum surface pressure did not exceed 0.4 mN/m upon compression during the three cycles, indicating that the spreading solvent is not surface active.Orbulescu et al105 have shown that spreading solvents such as chloroform, toluene, and benzene were not significantly surface active, when the maximum changes in surface pressure upon the compression of the pure solvent spread on the water subphase at 20 ± 0.5°C were less than 0.5 mN/m. Our data were in good agreement withOrbulescu et al, where maximum changes in surface pressure upon the compression of the spreading solvent (n-hexane:methanol 95:5 v/v) on the air-liquid interface were less than 0.4 mN/m.To ensure that the spreading solvent n-hexane:methanol (95:5 v/v) has the ability to efficiently spread DPPC at the air-liquid interface, γ min and γ max were measured during three compression-expansion cycles.Table 2-10 summarizes the surface properties of the air-liquid interface before and after the addition of DPPC.…”
mentioning
confidence: 99%